Prediction of sensation seeking and coping strategies based on emotional intelligence with the mediation of metacognitive beliefs in Qom province students - Alborzi, Mohammad Milad; Khosh Lahjeh Sedgh, Anis (Iranian Journal of Neurodevelopmental Disorders, 2023)
Purpose: The present study was conducted with the aim of predicting sensation seeking and coping strategies based on emotional intelligence with the mediation of metacognitive beliefs in Qom province students.Method: The research method was descriptive-correlation and specifically, structural equation modeling, and its statistical population consisted of all students of Qom universities in 1401. Among these people, a sample size of 200 people was selected according to the formula of Mears et al. (2006) with the available sampling method and using emotional intelligence questionnaires of Shot et al. Zuckerman's 5th form sensation seeking and Wells et al.'s metacognition questionnaire (2004) were evaluated. Research data were analyzed using descriptive (mean and standard deviation) and inferential (Pearson correlation test and structural equation model) statistical methods through SPSS-23 and AMOS-24 software.Findings: The results of the present study showed that there is a negative and significant relationship between the component of evaluation and expression of emotion, regulation of emotion, exploitation of emotion and the total score of emotional intelligence with the total score of sensation seeking in students and a positive and significant relationship with the total score of coping strategies and metacognitive beliefs. There is (p>0.01). Also, there is a negative and significant relationship between the components of negative beliefs, cognitive confidence and cognitive self-awareness with the total score of sensation seeking in students (p